AB0471 Risk Factors for Pregnancy Morbidity in Patients with Antiphospholipid Antibodies without A Defined Clinical Antiphospholipid Syndrome. (15th July 2016) - Demetrio Pablo, R.; Muñoz, P.; Riancho-Zarrabeitia, L.; Calvo-Río, V.; Lόpez-Hoyos, M.; Martínez-Taboada, V.M.
Abstract : Background: Antiphospholipid syndrome (APS) is an autoimmune disease characterized by the presence of either thrombosis or pregnancy morbidity and antiphospholipid antibodies (aPL), such as anticardiolipin (ACL), anti b2 glycoprotein (AB2GLP1) and lupus anticoagulant (LA). The prevalence of aPL is around 10% in the general population, increasing up to 50% in lupus patients. However, the frequency of pregnancy morbidity and the influence of the antibody profile in patients with positive APL serology without a defined APS is not well established. Objectives: 1) To define the frequency of pregnancy morbidity in women with positive aPL who do not fit the clinical criteria for APS; 2)To analyze the influence of the serological profile and the load of antibodies associated with these complications, and 3) To determine the efficacy of prophylactic treatment in preventing adverse pregnancy outcome. Methods: We retrospectively analyzed 92 pregnancies in 39 women with a confirmed positive serology for aPL (ACL, AB2GLP1 and LA) according to Sydney criteria. Then, we analyzed a subgroup of 15 women who had 38 pregnancies after a positive serology was confirmed. Results: Overall, 54% of the 39 pregnant women suffered morbidities: one early pregnancy loss (7), two pregnancies losses (7), fetal death* (1), premature birth* (1), preeclampsia (2) and intrauterine growth restriction (3). After a mean follow-up of 146±60, 3 months, only 2 patients developed obstetric APS* and none of them developed thrombotic APS. We found no association between the antibody profile and pregnancy morbidities. There was no association between pregnancy complications and the load of antibodies either. Regarding prophylactic treatment, only 8 women received AAS, combined with LWH in 3 of them, we found a non-significant tendency to prevent obstetric events. When analyzing the 92 pregnancies, we found 28 obstetric events in 26 pregnancies. Mean age for pregnant women was 29, 9±5, 8 years, gestational age was 38, 2±1, 8 weeks, birth weight was 3108±482 g and mean Apgar was 8, 7±1, 1. Regarding treatment influence there was a non significant tendency to prevent obstetric events (OR 0, 32, CI 95% 0, 87–1, 20; p=0, 081), that reached statistical significance when analyzing early pregnancy losses (OR 0, 12; IC 0, 02–0, 95; p=0, 019). When we restricted the analysis to the 38 pregnancies that were posterior to the positive serology result, we found a significant protective effect of prophylactic treatment (OR=0, 15; CI 95% 0, 02–0, 85; p=0, 021), thus conferring a 6.5-fold higher risk of pregnancy complications in the untreated women (IC 95% 1, 2–36, 33; p=0, 032). Conclusions: a) Pregnancy morbidity rate in women with positive antiphospholipid antibodies was 54% when analyzing the total number of pregnancies, and 32% when analyzing the pregnancies after confirmed positive serology. b) We didn't find a profile of antibodies specifically related with obstetric complications. c)Prophylactic drug therapy is effective in preventing early pregnancy losses and achieving a higher live birth rate. Disclosure of Interest: None declared